Students’ Insights on A-Z Glossary of Book and Publishing Terms for Junior High School - Deswita, Asni; Widya Safitri (BiCED Proceeding, 2024)
In the Indonesian educational system, English is a mandatory subject at both primary and secondary levels, as seen at SMP N 3 Ampek Angkek. Established as the first literacy based school in Agam Regency in 2018, the institution hosts an annual literacy expo and implements the “Satu Siswa Satu Buku, Satu Guru Satu Buku” (SASISABU) program, meaning “one book, one student” and “one book, one teacher.” This study aims to identify the students’ perception on supplementary English books designed to support students' understanding of publishing related vocabulary, aligned with the schools’ emphasis on literacy. Using a qualitative descriptive method, data were collected through questionnaires. Findings reveal positive response from the students, essential for students engaged in the literacy program. The lack of relevant publishing vocabulary in existing materials limits students’ ability to talk about literacy programs. This study highlights the potential for ESP (English for Specific Purposes) materials to enhance literacy-focused education by aligning language learning with real-world applications. The resulting glossary provides a model that other literacy-based schools may adopt.